National accounts statistics : sources and methods - Maurice, Rita.; Central Statistical Office (London : Her Majesty's Stationery Office, 1968)
This book provides a description of the national accounts for the United Kingdom. It describes the structure of the official accounts and the preparation of the estimates included in them
Includes bibliographical footnotes and index.
gp 21/01/2019
Loans
Keywords: National income--Accounting.; Statistics - national account; National accounts; Great Britain